2005
DOI: 10.1111/j.1440-1711.2005.01323.x
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species are essential mediators in antigen presentation by Kupffer cells

Abstract: Summary Kupffer cells (KC) act as APC in the liver and play a major role in the clearance of gut-derived antigens and pathogens entering the liver with portal venous blood. Antigen presentation by KC has been implicated in regulation of the local and systemic immune responses. In this study, modulation of KC antigen presentation by antioxidants and the role of reactive oxygen species (ROS) as essential mediators of antigen presentation in KC were investigated. Co-culture of KC with ovalbumin (OVA) antigens res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(55 citation statements)
references
References 28 publications
3
51
0
1
Order By: Relevance
“…It was expected that the miRNAs that are downregulated in samples in which controls were labeled with Cy3 and H 2 O 2 -treated samples with Cy5 ( Figure 2a) follow a reverse pattern in dye swapping and it was the case (Figure 2b). Furthermore, we verified in the microarray analysis that none of the miR- tive immune response by acting as a third signal for T cell activation by upregulating costimulatory molecules [4,36]. The fact that some of the target proteins of miR-27a* and miR-27b* are implicated in the activation of NF-kB prompted us to examine the effects of oxidative stress-responsive miRNAs in the modulation of the NF-kB pathway.…”
Section: Resultsmentioning
confidence: 99%
“…It was expected that the miRNAs that are downregulated in samples in which controls were labeled with Cy3 and H 2 O 2 -treated samples with Cy5 ( Figure 2a) follow a reverse pattern in dye swapping and it was the case (Figure 2b). Furthermore, we verified in the microarray analysis that none of the miR- tive immune response by acting as a third signal for T cell activation by upregulating costimulatory molecules [4,36]. The fact that some of the target proteins of miR-27a* and miR-27b* are implicated in the activation of NF-kB prompted us to examine the effects of oxidative stress-responsive miRNAs in the modulation of the NF-kB pathway.…”
Section: Resultsmentioning
confidence: 99%
“…However, additional pivotal effects of ROS include expanding the pool of mature DCs that express the costimulatory molecule CD80, and increasing DC mediated Ag presentation (37). Antioxidants potently inhibit DC differentiation and ability to activate T cells (60,61) in part by suppressing expression of MHC class II and costimulatory molecules in response to antigen (62). N-Acetyl-cystein (NAC), which acts as an intracellular scavenger of ROS by restoring intracellular concentrations of glutathione, can block DC maturation (63) and DC-mediated T cell activation (64).…”
Section: T Cells Mediate the Effects Of Estrogen Deficiency In Bonementioning
confidence: 99%
“…Furthermore, triggering of certain TLRs in immune cells results in formation of mROS important for bactericidal activity and for regulation of redox-sensitive signaling pathways regulating cytokine release and Ag-presenting capacity (22,26). It has been shown that ROS production in DCs upon communication with cocultured T cells determines their Ag-presentation capacity (46,47). In those studies, scavenging of ROS by antioxidants, resulted in reduced release of inflammatory cytokines such as IL-6, but also abrogated induction of MHC and costimulatory molecules.…”
Section: Discussionmentioning
confidence: 99%